A percepção da população sobre a Floresta Nacional de Passa Quatro (MG): um estudo sobre sua valoração econômica e retorno para sociedade local - Barreto, Ives Willian Kibaltchich [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
National Forest (FLONA), defined by SNUC, is a category of Conservation Unit (UC) for Sustainable Use. This category of UC is open to the practice of tourism, in addition to allowing the sustainable extraction of its resources. The case study in question is an analysis that permeates the vision and the environmental perception of the population of the municipality of Passa Quatro (MG), in relation to the importance of a conservation unit, and what economic role the National Forest of Passa Quatro plays for the municipality. In the Management Plan of the unit, prepared in 2009, it was identified that the general population presents little knowledge about general aspects that involve conservation units, FLONA itself, and basic environmental issues. Questionnaires were applied to 100 people of the municipality, in a random way, contemplating diverse visions and localities of the municipality that presents 16,413 inhabitants, besides another questionnaire for the manager and another 11 questionnaires for the employees. The present study presents an analysis with the answers of the questionnaires applied to the population, compared to the other two, allowing to conclude the little evolution of population knowledge about FLONA since the elaboration of the management plan, requiring a greater initiative of the UC to promote the area to be more than a tourist point, becoming an educational area on environmental issues, with more participation of the municipality

Floresta Nacional (FLONA), definido pelo SNUC, é uma categoria de Unidade de Conservação (UC) de Uso Sustentável. Essa categoria de UC é aberta à prática do turismo, além de permitir a extração sustentável de seus recursos. O estudo de caso em questão é uma análise que permeia a visão e a percepção ambiental da população do município de Passa Quatro (MG), em relação à importância de uma unidade de conservação, e qual o papel econômico que a Floresta Nacional de Passa Quatro desempenha para o município. No Plano de Manejo da unidade, elaborado em 2009, identificou que a população no geral apresenta pouco conhecimento sobre aspectos gerais que envolvem unidades de conservação, a própria FLONA, e questões básicas relacionadas ao meio ambiente. Foram aplicados questionários para 100 pessoas do município, de forma aleatória, contemplando diversas visões e localidades do município que apresenta 16.413 habitantes, além de um outro questionário para o gestor e outros 11 questionários para os funcionários. O presente estudo apresenta uma análise com as respostas dos questionários aplicados à população, comparadas aos outros dois, permitindo concluir a pouca evolução do conhecimento da população sobre a FLONA desde a elaboração do plano de manejo, necessitando uma maior iniciativa da UC em promover a área a ser mais que um ponto turístico, tornando-se uma área educativa acerca das questões ambientais, com mais participação do município
Keywords: Florestas; Unidades de conservação; Educação ambiental; Sustentabilidade; Ecologia humana; Turismo; Turismo sustentável; Manejo florestal; Reservas florestais; Minas Gerais